Differential effects of interleukin 6 immediately after acute social stress: preliminary results - Rodríguez Medina, David Alberto; Leija-Alva, Gerardo; Domínguez Trejo, Benjamín; Hernández-Pozo, María del Rocío; Vázquez-Ortega, José Joel (Entreciencias: Diálogos en la Sociedad del Conocimiento, 2020)
Purpose: To evaluate the differential effect of acute social stress on IL-6 using the Trier Social Stress Test (TSST). Methodology: Seventeen normotensive university students whose mean arterial pressure was recorded in three moments, 10 min before, pre and post TSST participated. A sample of salivary IL-6 pre-post TSST was also collected. Results: There was an increase in mean arterial pressure only when the TSST was present (p<0.001). The level of IL-6 pre-post TSST showed no statistically significant changes (p> 0.05). However, a thorough analysis of the effects of TSST on IL-6 revealed that 53 % of the sample increased their concentration of IL-6 (p <0.001) while 47 % of the participants decreased their IL-6 level (p <0.01); there is a statistically significant difference between these two subgroups (p<0.05). Limitations: It is recommended to establish normative parameters of salivary IL-6. Findings: The preliminary data we present suggests that acute social stress increases blood pressure, but that this effect induces a differential expression of IL-6 in all participants. In participants with a low concentration of IL-6, it increases after acute stress, while for those with a previous high level of IL-6, the test tends to decrease it.